Atacamite Cu2Cl(OH)3: A model compound for the S = 1/2 sawtooth chain? - Heinze, L.; Jeschke, H.; Metavitsiadis, A.; Reehuis, M.; Feyerherm, R.; Hoffmann, J. U.; Wolter, A. U. B.; Ding, X.; Zapf, V.; Corvalán Moya, Carolina del Huerto; Weickert, F.; Jaime, M.; et al. (American Physical Society, 2019)
Fil: Heinze, L.. Technische Universitat Carolo Wilhelmina Zu Braunschweig.; Alemania